Subclasses of Harmonic Mappings Defined by Convolution. (8th April 2013) - Joshi, Santosh B.; Shelake, Girish D.
Abstract : Two new subclasses of harmonic univalent functions defined by using convolution and integral convolution are introduced. These subclasses generate several known and new subclasses of harmonic univalent functions as special cases and provide a unified treatment in the study of these classes. Coefficient bounds, extreme points, distortion bounds, convolution conditions, and convex combination are also determined.